Exploring Hepatitis From the Perspective of Iranian Traditional Medicine: Using a Qualitative Approach. (April 2017) - Yousefi, Mahdi; Hosseini, Seyed Mous al-Reza; Taghipour, Ali; Zibaee, Saeed; Noras, Mohammad Reza
Hepatitis is a global health problem, with significant adverse impacts on patients' quality of life. In this study, we aimed to review major resources of Iranian traditional medicine and determine whether the etiology and semiology of hepatitis, in particular chronic hepatitis, in traditional and conventional medicine might be aligned. Through such studies, we might be able to develop new approaches for clinical research to improve our current knowledge on the etiology and treatment of this condition. In this qualitative study, recently published studies, scientific databases, and reliable Iranian traditional medicine resources, including the Canon of Medicine, were searched. The integrative use of conventional and traditional medicine for diagnostic and therapeutic purposes could be evaluated to develop new modalities for dealing with this condition. An integrated approach is recommended in clinical research in order to find more efficient and safer treatment.